FULFILLING CHILDREN'S EDUCATIONAL RIGHTS AFTER DIVORCE: A NORMATIVE ANALYSIS OF INDONESIAN PARENTAL OBLIGATIONS - Naquita Khairana Rizvi; Galilea Emona Ermadi (STKIP Subang, 2026)
Divorce terminates the marital bond but does not extinguish parental responsibility for children's education. This study analyzes the legal construction of post-divorce parental obligations, the barriers to fulfilling educational rights, and the institutional implications for primary schools. It employs normative juridical research using statutory, conceptual, and limited case approaches. Primary legal materials comprise Indonesian marriage, child protection, education, civil, and Islamic family law, supported by judicial policies and recent studies on child support and elementary pupils' learning motivation. The analysis finds that: first, both parents remain responsible for maintenance, education, protection, and meaningful contact after divorce; second, fragmented regulations converge on the best-interests-of-the-child principle and require educational costs to be treated as a continuing, needs-based obligation; and third, weak pleading, vague judgments, costly execution, unstable income, and parental conflict frequently transform formal rights into non-enforceable promises. The article proposes an integrated model combining detailed judicial orders, periodic adjustment and compliance monitoring, cooperative parenting, and confidential school-based support. Its contribution is to connect family-law enforcement with educational continuity, clarifying that schools support pupils' learning and well-being without replacing courts or adjudicating parental disputes.